If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 8(x + -5) = 2 + -2(x + -2) Reorder the terms: 5 + 8(-5 + x) = 2 + -2(x + -2) 5 + (-5 * 8 + x * 8) = 2 + -2(x + -2) 5 + (-40 + 8x) = 2 + -2(x + -2) Combine like terms: 5 + -40 = -35 -35 + 8x = 2 + -2(x + -2) Reorder the terms: -35 + 8x = 2 + -2(-2 + x) -35 + 8x = 2 + (-2 * -2 + x * -2) -35 + 8x = 2 + (4 + -2x) Combine like terms: 2 + 4 = 6 -35 + 8x = 6 + -2x Solving -35 + 8x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -35 + 8x + 2x = 6 + -2x + 2x Combine like terms: 8x + 2x = 10x -35 + 10x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 -35 + 10x = 6 + 0 -35 + 10x = 6 Add '35' to each side of the equation. -35 + 35 + 10x = 6 + 35 Combine like terms: -35 + 35 = 0 0 + 10x = 6 + 35 10x = 6 + 35 Combine like terms: 6 + 35 = 41 10x = 41 Divide each side by '10'. x = 4.1 Simplifying x = 4.1
| 10m+70=10m+10-16m | | 10(2+x)+0=6 | | -3(r+2)=-15 | | 2w+10=60 | | 2n+1+n=-8 | | W/5=24-4 | | X-13-2x=2 | | 2x^3+12x^2+16x=y | | 18p+q+3p+12q= | | x+78=72 | | 3(5x-8)-6x+20=-22 | | X+99=93 | | 4(3r-4)=3(r+9)+2 | | b-1/2=2 | | 3(Y+9)+3Y=30 | | 10+6a=-104 | | f(x)=3x^2+5x+7 | | X/2-430 | | 2(t+8)=8 | | 9x-6=7y+3x | | 5y+6q=20 | | 200+.62x=379.8 | | 4x^2-10x-126=0 | | 2x-x=-1+3 | | 200-.62x=379.8 | | 24a^3b^2-16a^2b^3/8ab | | 5y-8/8-5y | | 5(4a+3b)5(2a+3b)= | | 2/5x-1-9/4x-6 | | 25x-21=16x-4x | | 3(y+9)1y=30 | | (2x-5)/(x-1)3 |